Selfishness, greed and capitalism : debunking myths about the free market - Snowdon, Christopher (Hobart paper, 2015)
This IEA publication deals head-on with a number of widely quoted myths about the market economy. In the case of the philosophical myths, such as the idea that economists believe that everybody is greedy, the author, Christopher Snowdon, carefully and entertainingly unpicks the misguided ideas that have taken hold. The author then moves on and effectively disposes of a number of economic myths using empirical evidence that is often ignored by commentators.